Toxicological evaluation of feed contaminated with herbicides using luminescent microorganisms Photobacterium Phosphoreum - Kurbatska, O; Orobchenko, O; Kolchyk, O; Dukhnytskyi, V (Journal of the Hellenic Veterinary Medical Society, 2025)
Based on the reduction in luminescence intensity, a rapid toxicological assessment (up to 30 minutes) of herbicide-contaminated feed can be performed using the luminescent microorganisms Photobacterium phosphoreum (strain IMB B-7071; Sq3). However, for the herbicides Greenfort Horse (chisalofop-p-ethyl) and Astralid (clopyralid), when tested at the maximum residue limit (MRL) levels (0.04 and 2.0 mg/kg), the feed was classified as non-toxic. While for the herbicides Skat (chisalofop-p-tefuryl), Agroshield Super (glyphosate potash), Greenfort Extra (metolachlor+terbutazine) and Greenfort NK 40 (nicosulfuron) MRL (0.04; 1.0; 0.1 and 0.2 mg/kg) feed is classified as toxic for Soteira (imazamox+imazapyr), Greenfort Premium (2,4-D 2-ethylhexyl ether+florazulam) and Astanes (acetochlor) (MRL 0.05; 0.05 and 0.03 mg/kg) – classified as extremely toxic, indicating the need for further studies on the toxicological properties of the herbicide in laboratory and farm animals and possible further (downward) feed revision the maximum allowable levels of relevant pollutants.